Analisis Demokrasi di Indonesia: Praktik Kekuasaan dan Partisipasi Masyarakat Sipil dalam Pemilu Tahun 2024 - Binti Masruroh (Jurnal Sosial dan Humaniora, 2025)
Democracy in Indonesia after the reform era has normatively progressed through regular elections and relatively open political freedom. However, in practice, this democracy shows various symptoms of decline or democratic injury. This article aims to analyze the condition of Indonesia's injured democracy through a political sociology perspective. The method used is a literature study with a descriptive-critical approach to state policy, the practice of power, and the dynamics of community participation. The results of the study show that the damage to democracy in Indonesia is characterized by the strengthening of oligarchy, the weakening of democratic institutions, restrictions on civil space, and the reduction of citizen political participation to a mere procedural matter. This article emphasizes that democracy cannot be understood merely as an electoral mechanism, but as a social practice that demands justice, freedom, and substantive participation.